Psychiatric Health Problems and Health Seeking Behavior of Men Who Have Sex with Men (MSM) in Agra city, Uttar Pradesh - Khan Iqbal Aqeel; S.S. Chaudhary; Geetu Singh; S.K. Misra (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Researches had shown that Men who have sex with men (MSM) have higher chances of having psychiatric disorder as compared to heterosexual men. Ongoing homophobia, stigma and discrimination have negative effects on mental health of MSM. Many MSM do not seek care from mental health provider because of fear of discrimination Objectives: This study was carried out to assess psychiatric health problem among MSM and also assess their health seeking behavior. Method: The Snowball sampling technique was used. First participants were recruited through a non-profit peer group. Further participants were subsequently referred by participants from their peer circles. Data obtained from total 52 MSM using pretested questionnaire and General health questionnaire (GHQ-28) was analyzed using MS Excel. Results: Two-fifth (40.38%) of MSM had self-reported psychiatric health problem. While on GHQ, 57.69% of MSM were found to have psychiatric health problem with GHQ score of ≥24. MSM who were completely homosexual and who were victims/doer of violence with sex partners had significantly higher chances of having psychiatric health problem.57.15% MSM sought treatment for their psychiatric problem from an Allopathic doctor. Rest of them either went for a self treatment (28.57%) or not taken any treatment (14.28%). 75% MSM reportedly sought treatment from private health facility. Better facility, cost effectiveness, someone known recommended were most commonly cited reason for preferring a mental health provider. Conclusion: High prevalence of psychiatric health problems was found among MSM who engage in higher-risk sexual behavior. MSM require access to mental health screening services.